Features of the use of anthroponyms as place names in Uzbek and English - Muxitdinova , Xadicha; To‘laganova , Nargiza (The Lingua Spectrum, 2025)
The article covers the issue of the onomastic field of linguistics, which studies names, its important practical importance in understanding the connections between language, culture and history. The study investigated the scale and layers of onomastics, the correlation between name categories, the dynamic nature of anthroponyms representing individual names, and investigated the expanding socio-functional functions of individual names as a result of the influence of socio-historical changes in society. In particular, the fact that different Ethnos represent toponymic object names of anthroponyms in social, historical and geographical contexts leads to an expansion of the socio-political functions of individual names has been analyzed on the example of anthroponyms in Uzbek and English. These analytical results also show that nouns serve to encompass social hierarchies, not only in the identity quality of national-cultural values, historical contexts. The article is also of theoretical and practical importance in terms of revealing similarities and discrepancies in the use of anthroponyms as toponyms in Uzbek and English. This study uses comparative linguistic analysis to study the use of anthroponyms as toponyms in Uzbek and English. The data was collected from historical records, linguistic studies and cultural references, and examples were analyzed to determine the laws of converting personal names into place names. The study aims to identify the following: Historical and geographical factors affecting the formation of names. Sociolinguistic functions of nouns in cultural and regional contexts. Cross-linguistic comparisons to reveal universal and language-specific trends.